Autonomy and vulnerability: elements of a phenomenology of reflection and reason - Melichar, Gustav (Human studies, 2025)
Large parts of the Western philosophical tradition, powerful in Kant’s transcendental conception, have reserved the concept of autonomy for rational subjects that think and act on reasons. While this captures an essential aspect of autonomy, the dimensions of embodiment and vulnerability remain unreflected or are subsumed under the heteronomous conditions of the human subject. If the conception of autonomy, though, doesn’t start with the concept of a rational subject but from the perspective of living beings, autonomy and vulnerability seem intrinsically connected, as Jonas’ (1973; 1997) concept of “needful freedom” suggests. This article argues for a deep connection between human autonomy and vulnerability. Methodologically, the argument follows the life-mind-continuity thesis (Thompson, 2007) and lays out the embodied account of autonomy that enactivism offers. Two crucial moments are: 1. The organism can distance itself from the environment. 2. This enables it to establish its own norms. However, the norms of bodily self-regulation also render the organism vulnerable. This conception, though, needs specification for capturing human autonomy. As enactivists like E. Thompson assume, phenomenology is essential to theorizing about human autonomy. I will develop a phenomenological concept of autonomy starting from three notions of selfhood (Zahavi, 2008) and arguing for a central role of the reflective self for human autonomy. Reflection grounds both moments of autonomy: Self-distancing and the possibility of taking a stance by relying on reasons. In the phenomenological sense, autonomy is thus the ability to respond to reasons for which reflection is necessary. However, this ability is bound to a particular form of vulnerability that manifests in some psychopathologies. This vulnerability will be shown in conclusion by Blankenburg’s reflections on the role of autonomy in mental diseases.
Gesehen am 31.03.2025
Online veröffentlicht: 7. Januar 2025